Approaches to Build a Motivation System for Healthcare Workers Through Studying Their Needs - E. A. Konovalova (Здоровье мегаполиса, 2025)
Background. Being valuable resources of primary healthcare organizations, healthcare workers ensure the quality of medical care and fulfill healthcare tasks in preserving national health. Primary care providers suffer from chronic stress due to various factors: a permanent staff shortage, a need to strictly follow standards and regulations that define time limits for interacting with patients, a high probability of conflicts, including misunderstandings of worker actions by patients. Thus, there is an obvious need to develop a motivation system for primary care providers.Purpose. To study motivational preferences and to analyze needs that lay the foundation to build an efficient motivation system for primary care providers.Materials and methods. Methods of analysis, synthesis, and content analysis were used to review scientific literature. The publications of Russian authors investigating the needs of primary care providers provided a basis for the study.Results. The study revealed the difficulties in building a motivation system based on the staff needs since the task has a multidimensional nature. Needs vary over employees and time, therefore, it is recommended, firstly, to carry out constant monitoring in order to timely identify the most significant transformations, secondly, to engage managers with knowledge and experience in motivation management and psychologists in building a motivation system in order to communicate more productively with staff.